Backlash and Beyond: The Criminalization of Agrarian Reform and Peasant Response in the Philippines - Jennifer Franco (Oñati Socio-Legal Series, 2014)
In the 35 years since the end of the dictatorship in the Philippines many rural poor Filipinos have been caught up in a political battle over the pace and direction of agrarian change. This paper focuses on the political-legal dimension of agrarian conflict in one region, exploring how it has fueled and been fueled by criminalization, particularly the indiscriminate filing of criminal charges against share tenants struggling for recognition as legal land rights holders under the 1988 agrarian reform law. Here, criminalization is a form of landlord retribution against tenants who dare to defy the status quo. The case demonstrates how tenants get “bound by law” – e.g., caught up in inconsistencies in state law and ensnared in costly legalist traps set by powerful landowners threatened with redistribution, but then also leading to innovative collective efforts to activate state officials to step in on the side of peasants to make state law authoritative in society. En los 35 años transcurridos desde el final de la dictadura en Filipinas muchos filipinos pobres de zonas rurales se han visto atrapados en una batalla política por el ritmo y la dirección del cambio agrario. Este artículo se centra en la dimensión político-jurídica del conflicto agrario en una región, analizando cómo ha impulsado y ha sido impulsado por la criminalización, especialmente la presentación indiscriminada de cargos penales contra los aparceros que luchan por que se les reconozcan los derechos de tierra legales, bajo la ley de reforma agraria de 1988. En este caso, la criminalización es la forma que tienen los terratenientes de responder contra los aparceros que osan desafiar el status quo. El caso demuestra cómo los arrendadores están "obligados por ley" - por ejemplo, están inmersos en incoherencias en la ley estatal y atrapados en costosas trampas legalistas puestas por los poderosos terratenientes amenazados con la redistribución, pero al mismo tiempo lideran esfuerzos colectivos innovadores para hacer que los funcionarios estatales se muevan a favor de los agricultores, y conseguir que la ley estatal sea autorizada en sociedad.